Creating Sustainable Photovoltaics for Smart Cities - Werner Brenner; Nadja Adamovic (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Research on solar energy systems and materials has yielded promising opportunities for sustainable energy solutions, which do not only consider environmental issues but also allow aesthetic design possibilities. New requirements regarding the energy efficiency performance of buildings gave the basis for two European projects aiming at sustainable energy solutions, which consider both environmental issues and aesthetic design. All research findings were expected to be in line with the EU's Waste Electrical and Electronic Equipment (WEEE) directive. FP7 SolarDesign put a focus on novel printing and scribing methods which make possible the manufacturing of flexible monolithically interconnected photovoltaic modules to be integrated into both devices and building envelopes. This technology allows customization of the PV modules' shape, size and voltage. SolarDesign developed a solar foil with a width of 300mm, basis for curved solar cells with a minimum radius of 10mm. The H2020 project CABRISS contributes to a circular economy that manages the critical situation of recycling a significant volume of photovoltaic waste. The project also contributes to electronics, metallurgy and glass industries. CABRISS comprises the development of: (i) recycling technologies to recover In, Ag and Si, (ii) demonstrating the possibility for the re-usability and recyclability of end-of-life key PV materials. Both projects involved European standardization bodies (CEN/CENELEC, SEMI).
Keywords: O32; 330; photovoltaics PV; circular economy; standardization; innovation; technology; sustainability; smart cities